간호대학생의 임상실습 스트레스, 우울 및 자기효능감 비교연구: Type D 성격군과 non-Type D 성격군을 중심으로 - 성미현; Seong Mi Hyeon; 김옥선; Kim Ok Sun; 정연옥; Jung Youn Ok; 석소현; Sok Sohyune (정신간호학회지, 2017)
The purpose of study was to examine and compare the clinical practicum stress, depression, and self-efficacy between Type D and non-Type D personality among nursing students. Methods: This study used a descriptive correlational survey design. Subjects included a total of 120 nursing students (Type D personality: n=60, non-Type D personality: n=60) in Seoul, Korea. The collected data were analyzed using a descriptive statistics, x 2 test, Fisher`s exact test, independent t-test, ANCOVA, and Scheffe test as a post hoc test with SPSS/WIN 21.0 program. Result: There were significant differences on clinical practicum stress (t=2.81, p=.029), depression (t=6.67, p<.001), and self-efficacy (t=9.84. p<.001) between non-Type D and Type D personality among nursing students. Conclusion: Type D personality in nursing students had higher clinical practicum stress and depression than them of non-Type D personality in nursing students. Nursing interventions or strategies for Type D personality in nursing students are needed to decrease clinical practicum stress and depression.